(untitled) (Conference on English Language Teaching, 2023)
This study was aimed to investigate gender representation in an English Textbook entitled Student’s Book My Next Words for Elementary School which published by The Republic of Indonesia’s Ministry of Education and Culture in 2021. Porecca’ (1984) framework was adopted for analyzing the female and male representation in the English textbook: omission (the ratio of females to males) in texts and illustrations, firstness, occupational visibility, noun, masculine generic construction, and adjective. The visibility of gender imbalance was found in the textbook. The number of visibility data depicted that male was higher than female. For social dominance was not found in the textbook. However, the variant of firstness, occupation, noun, masculine generic, and adjective for males are varier than for females. Some stereotypes were found such as cooking for females’ activity and the breadwinner role for males. A limitation of the study is that it focuses on one textbook only. Thus, this study can’t be generalized. For this purpose, another study with a larger sample would be required a deeper analysis of the picture of the EFL textbook.